Active force control with input shaping technique for a suspension system - Md. Zain, M. Z.; Mailah, Musa; Priyandoko, G. (Faculty of Mechanical Engineering, 2008)
This paper describes an approach to investigate and develop a hybrid control scheme for vibration suppression of a vehicle suspension system. Initially, an active force control (AFC) scheme is developed for the motion control of the system. This is then extended to incorporate a feed forward controller based on an input shaping (IS) technique for the control of vibration of the suspension system that could in turn lead to the enhancement of the riding performance of the vehicle. Simulation results of the response of the suspension system with the proposed control scheme are presented in time and frequency domains. The performance of the hybrid control scheme with AFC and IS control are particularly assessed in terms of the level of vibration reduction.